Islamic Financial Literacy Analysis of Islamic Economics Students using The Theory of Planned Behavior (TPB): Empirical Studies with SEM-PLS Approach - Iqbal ‘Imari; Hartomi Maulana; Ahmad Suminto; Willy Tambayong; Soritua Ahmad Ramdani Harahap (Proceedings of Femfest International Conference on Economics, Management, and Business, 2023)
After the merger, Islamic banks are expected to be able to break the growth of public interest in saving in Islamic banks, because they inherit the good things from each merger bank, namely BNI syariah with its innovations, Mandiri Syariah with its professional system and BRI syariah with a widespread local understanding, in recent years has increased but not much, in this case, it will be seen interest in Islamic banks through students as a benchmark. Seeing that the student's interest in Islamic banking is quite low, so researchers want to see the extent to which Islamic financial literacy in young students is more focused on saving in Islamic banking, so the purpose of this research is to analyze Islamic financial literacy in Islamic economics students. It is located in several universities are especially for students of Islamic economics. This research uses quantitative methods using the Structural Equation Modeling-Partial Least Square (SEM-PLS) tool and uses the Theory of Planned Behavior as a measuring factor. The results of this research were obtained that attitudes, subjective norms, and perceptions of behavioral control had a significant positive effect on students interest in saving in Islamic banks.